The Concept of Fostering Muhammadiyah in Producing Progressive Cadres - Husna, Difaul; Saudah , Bunan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
As an Islamic movement and da'wah of Amar Ma'ruf Nahi Mungkar, which are sourced from the Quran and sunnah, Muhammadiyah needs to move in the regeneration process for the creation of progress or civilization. The purpose of this study is to know the concept of Muhammadiyah cadre development at the Muhammadiyah Boarding School Pleret Bantul Yogyakarta. This research is field research using a qualitative descriptive approach. This approach is intended to collect in-depth information about the development of Muhammadiyah cadres in the Muhammadiyah Boarding School Pleret Bantul Yogyakarta and get appropriate results from field research. Data collection is carried out through observation, interviews, and documentation. In addition, researchers collect data by triangulation, which is collecting data while testing the credibility of the data by comparing various data collection techniques and various data sources. After all the data is collected, data analysis is carried out by reducing the data, presenting the data, and drawing conclusions. The results showed that the development of Muhammadiyah cadres was carried out through learning activities, organizations, and islamic boarding schools. The implementation of the development of Muhammadiyah cadres is divided into three stages, namely preparation, implementation, and evaluation